SEG Technical Program Expanded Abstracts 2010 2010
DOI: 10.1190/1.3513351
|View full text |Cite
|
Sign up to set email alerts
|

Advances in experimental research of induced polarization effect in reservoir rocks

Abstract: We have studied the IP response of the multiphase porous systems by conducting complex resistivity (CR) frequency domain IP measurements for two different groups of samples: sands and sandstones containing salt water in pores and those whose unsaturated pores are filled with synthetic oil. We have observed the IP behavior in the imaginary parts of the analyzed complex resistivity curves. We have studied statistical aspects of CR measurements in HC-saturated samples using sand-cartridge-oil (SCO) and sandstone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…We have also studied the IP effect in multiphase porous rocks in view of possible application in a HC exploration. The results of this study demonstrated that a resistivity of reservoir rocks saturated with the mixture of water and oil is complex and frequency dependent and that the oil-saturated sands and sandstone samples can be characterized by a significant IP response [32][33][34]. Similar results were also reported in the papers by Revil et al (2012Revil et al ( , 2013 [35,36].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have also studied the IP effect in multiphase porous rocks in view of possible application in a HC exploration. The results of this study demonstrated that a resistivity of reservoir rocks saturated with the mixture of water and oil is complex and frequency dependent and that the oil-saturated sands and sandstone samples can be characterized by a significant IP response [32][33][34]. Similar results were also reported in the papers by Revil et al (2012Revil et al ( , 2013 [35,36].…”
Section: Introductionsupporting
confidence: 86%
“…This model was applied for GEMTIP fit of the experimental data at early stages of our research [32,33]. …”
Section: Development Of Effective-medium Model With Random Spherical mentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients lα γ and lα λ are the structural parameters defined by geometrical characteristics of the ellipsoidal inclusions (Zhdanov, 2008;Burtman et al, 2010), and they are functions of ellipticity e l . If all the grains are oriented in one specific direction, the effective conductivity of this medium will become anisotropic.…”
Section: Effective-medium Model Formentioning
confidence: 99%
“…The expression for GEMTIP model in this case takes the following form: [33], and they are functions of ellipticity e l . If all the grains are oriented in one specific direction, the effective conductivity of this medium will become anisotropic.…”
Section: Effective-medium Model For Analysis Of Complex Resistivity Imentioning
confidence: 99%